Cэргээгдэх эрчим хүчийг дэмжих замаар эрчим хүчний үйлдвэрлэлээс үүсэх хүлэмжийн хийн ялгарлыг бууруулах боломж - Д.Сандэлгэр; С.Эрдэнэсүх (Geological Issues, 2023)
Share of greenhouse gas (GHG) emissions by energy production sector are about 30% in total GHG emission by Mongolia while it is about 60% of total emissions by the total energy sector. Thus, this study presents some results of potential emission reductions of greenhouse gas by the energy production sector based on the increase in the share of renewable in electricity production using greenhouse gas emission data, demographic end economic data of Mongolia, energy balance data, and transport data are taken from national and international various sources. LEAP model that plans future of energy sector and some scientific tools were used for the computation of projection of GHG emission and its reduction for a period from 2010 to 2030.